2018
DOI: 10.1371/journal.pgen.1007586
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of gene expression traits across diverse populations

Abstract: For many complex traits, gene regulation is likely to play a crucial mechanistic role. How the genetic architectures of complex traits vary between populations and subsequent effects on genetic prediction are not well understood, in part due to the historical paucity of GWAS in populations of non-European ancestry. We used data from the MESA (Multi-Ethnic Study of Atherosclerosis) cohort to characterize the genetic architecture of gene expression within and between diverse populations. Genotype and monocyte ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
119
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 51 publications
13
119
0
Order By: Relevance
“…However MESA_AFA contains the models that should best reflect the genetic ancestry of African Americans in SAGE (Supplementary Table 1). We note that MESA_AFA also has the smallest training sample size among our weight sets (N = 233)[38], so the small number of predicted genes from MESA_AFA probably results from the small training sample size and not from any feature of the underlying MESA_AFA training data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However MESA_AFA contains the models that should best reflect the genetic ancestry of African Americans in SAGE (Supplementary Table 1). We note that MESA_AFA also has the smallest training sample size among our weight sets (N = 233)[38], so the small number of predicted genes from MESA_AFA probably results from the small training sample size and not from any feature of the underlying MESA_AFA training data.…”
Section: Resultsmentioning
confidence: 99%
“…Among TWAS resources, we focused on PrediXcan as a test case with openly distributed prediction models available for multiple populations. [6, 38] Using 39 subjects from the SAGE study[39–42] we compared predicted expression values from PrediXcan models to measured gene expression on the same subjects and found that predictions matched poorly to measurements. Our investigation with the GEUVADIS dataset[43] offered us a more homogenous environment in which to train and test gene expression prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though most of the results were from the 44 predominantly European GTEx tissue 121 models, we also had significant PrediXcan results using the five MESA monocyte models built in various ethnicities [14]. 14/59 of the significant associations in HCHS/SoL were in MESA models, with 4 associations in CETP and 10 associations in 124 PSRC1 in the same effect direction as the other tissues (Table 2).…”
mentioning
confidence: 85%
“…MESA individuals include those that self-identified as "Black, African-American" (AFA, 295 n = 613), "White, Caucasian" (CAU = 2,243), and "Hispanic" (HIS, n = 999). Cohorts 296 underwent quality control and imputation as previously performed by our group [14]. (Fig.…”
mentioning
confidence: 99%